The 2014-15 eruption and the short-term geochemical evolution of the Fogo volcano (Cape Verde): evidence for small-scale mantle heterogeneity - Mata, J. (2017)
Recurrent eruptions at very active ocean island volcanoes provide the ideal means to gain insight on the scale of spatial variations at the mantle source and on temporal changes of magma genesis and evolution processes. In 2014, after 19 years of quiescence, Fogo volcano (Cape Verde Archipelago) experienced a new eruption, with the vents located 200 m from those of the 1995 eruption, and less than 2000 m from those of the 1951 event. This offered a unique opportunity to investigate the existence of small-scale mantle heterogeneities and the short-term compositional evolution of magmas erupted by a very active oceanic volcano like Fogo. Here we present petrological and geochemical data from the early stages of the Fogo's most recent eruption - started on November 23, 2014 - and compare them with the signature of previous eruptions (particularly those of 1995 and 1951). The magmas erupted in 2014 are alkaline (up to 23.4% and 0.94% of normative ne and lc, respectively) with somewhat evolved compositions (Mg # < 56), ranging from tephrites to phonotephrites. The eruption of phonotephritic lavas preceded the effusion of tephritic ones. Lavas carried to the surface clinopyroxene and kaersutite phenocrysts and cognate megacrysts, which indicate that the main stages of magma evolution occurred in magma chambers most probably located at mantle depths (25.6 5.5 km below sea level). This was followed by a shallower (<1.5 km below sea level) and shorter (approximate to 50 days) magma stagnation before the eruption. 2014 magmas have more unradiogenic Sr and more radiogenic Nd compositions than those of the previous 1951 and 1995 eruptions, which generally have less radiogenic Pb ratios. These isotopic differences- coming from quasi-coeval materials erupted almost in the same place- are remarkable and reflect the small-scale heterogeneity of the underlying mantle source. Moreover, they reflect the limited isotopic averaging of the source composition during partial melting events as well as the inefficient homogenization within the plumbing system when on route to the surface. The lid effect of an old and thick lithosphere is considered of utmost importance to the preservation of a significant part of source heterogeneity by erupted magmas. The decrease in the contribution of an enriched component to the Fogo magmas in the 2014 eruption marks a change on the volcano shortterm evolution that was characterized by a progressive increase of the importance of such a component. Nb/U ratios of the 2014 lavas are similar, within 2 sigma, to the mean value of OIB, but significantly lower than those reported for the 1995 and 1951 eruptions. This is considered to reflect the lack of significant mixing of the 2014 magmas with lithospheric melts, as opposed to what is here hypothesised for the two previous eruptions.